The one-child policy and its consequences: Asia and the Balkans - Lazarević Dajana (Srpska Politička Misao)
The one-child policy first appeared in the framework of legal regulations in the Republic of China in 1979. According to traditional Chinese beliefs, families with a male heir were considered more respectable and prosperous than families with a female heir. As a large number of families wanted to ensure a male heir and, at the same time, to avoid punishment for exceeding the permitted number of children, parents decided on various methods, which today we would call inhumane and criminal. From selective abortions to hiding the birth of female children, who suffered abuse, starvation, and often brutally killed. We will dwell in particular on the phenomenon of selective abortions, which is not only characteristic of China but also the more significant part of Asia and has also reached the Balkans. The paper before the readers does not represent a mirror of the positions of ProLife or ProChoice when it comes to abortions. This paper presents an objective, multidisciplinary view of the phenomenon of selective abortions, which appeared first in the People's Republic of China as a result of the introduction of the "one-child policy." Later, it came to India and the Arab world, and for the last two decades, it has also been practiced in certain countries of the Balkans (Albania, North Macedonia, and Montenegro). The socalled "son preference" reasons differ: value system, upbringing, and socio-economic reasons. However, the consequences of doing so are unfathomable since the natural demographic balance between the number of male and female members is disturbed.